Detection of an atypical 7q11.23 deletion in Williams syndrome patients which does not include the STX1A and FZD3 genes. Issue 6 (1st June 1999) - Botta, A; Novelli, G; Mari, A; Novelli, A; Sabani, M; Korenberg, J; Osborne, L R; Digilio, M C; Giannotti, A; Dallapiccola, B
Abstract : We present two patients with the full Williams syndrome (WS) phenotype carrying a smaller deletion than typically observed. The deleted region spans from the elastin gene to marker D7S1870. This observation narrows the minimal region of deletion in WS and suggests that the syntaxin 1A and frizzled genes are not responsible for the major features of this developmental disorder and provides important insight into understanding the genotype-phenotype correlation in WS.